2020
DOI: 10.1186/s13643-020-01408-4
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of family caregivers living with breast cancer patients in low-and middle-income countries: a systematic review

Abstract: Introduction: Caregivers of women with breast cancer in low-and-middle-income countries experience significant physical and economic burdens. The review aimed to map the evidence of studies that had reported on the experiences of family caregivers of women diagnosed with breast cancer. Methods: A systematic literature search was conducted in CINAHL, PubMed, PsycINFO, Scopus, and Web of Science databases using a combination of key search terms and medical subject heading terms such as "family caregiver," "breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 29 publications
6
56
0
1
Order By: Relevance
“…"The provision of informational support aided in decreasing caregiving burden among the caregivers." ( [40], p. 17) 2.4. Personal conditions Inductive T66.…”
Section: Inductivementioning
confidence: 98%
See 2 more Smart Citations
“…"The provision of informational support aided in decreasing caregiving burden among the caregivers." ( [40], p. 17) 2.4. Personal conditions Inductive T66.…”
Section: Inductivementioning
confidence: 98%
“…"religious coping such as putting one's faith in God was vital in improving the quality of life among caregivers. Two of the studies further reported that caregivers reported that being religious provided them with meaning in their caregiving roles"... "Previous knowledge on breast cancer aided caregivers to cope effectively in their caring role" ( [40], p. 15) T68. "The caregiver... must have a high motivation to adhere to his or her caregiving role.…”
Section: Inductivementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, breast cancer is the most common cancer type among females globally, and it is also one of the malignant tumours that seriously affect women's health (Tsaras et al., 2018). Different treatments and long‐term exposure to breast cancer become a huge burden for both the patients and their caregivers (Kusi et al, 2020). It also affects the mental health of patients, inducing problems such as symptoms of depression and anxiety (Ecclestone et al., 2016; Kale & Carroll, 2016; Kugbey et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to focus our scoping review on gaps in the evidence synthesis literature, we have also excluded parents or caregivers (unless part of the household) of cancer survivors from our study population, as well as studies specifically focused on occupational outcomes such as employment status, productivity loss (if measured in work hours or days), return-to-work or unmet financial needs. These exclusions are based on our awareness of more rigorous evidence synthesis studies such as systematic reviews that looked at caregivers of patients with cancer 38 or more specifically parents of patients with cancer, 36 FT, 34 financial hardship, 13 return-to-work after a cancer diagnosis, 8 as well as work productivity after cancer. 39 Our scoping review will provide synthesised evidence on the extent of the effect of a cancer diagnosis on the income of adults of different sexes, age groups, cancer types, geographical locations (ie, country of residence) and follow-up periods.…”
Section: Study Rationalementioning
confidence: 99%